Representations by Caregivers, Teachers, and Children on Food, Nutrition, Health, and School Breakfast Contributions for the “ESNUT” Nutritional Stabilization Program - Gallegos Martínez, Josefina; Reyes Hernández, Jaime (Investigación y Educación en Enfermería, 2016)
Objective. This work sought to determine the social representations conferred by caregivers, teachers, and children to food, health, and nutrition and the school breakfast program for children from three to seven years of age in the city of San Luis Potosí, San Luis Potosí, Mexico, through identifying a) knowledge and practices and b) meanings attributed on health and nutrition of children from three to seven years of age and on the school breakfast program. Methods. This was a qualitative health study. The sample included 33 mothers, 3 grandmothers, 1 father, 30 children from 3 to 7 years of age, and 8 teachers who signed an informed consent. The data were collected through a semi-structured interview and treated through content analysis modality thematic analysis. Results. The analysis yielded the categories: knowledge on food, the health-feeding relation, customs and practices of the child’s feeding, and meanings of the school breakfast program. Conclusion. On the reflection on the representations of the different players included in the school breakfast program, elements become manifest that would support an educational intervention by nursing, which would have to be based on the family as the central figure to provide good nutrition and teach good habits. How to cite this article: Gallegos-Martínez J, Reyes- Hernández J. Representations by Caregivers, Teachers, and Children on Food, Nutrition, Health, and School Breakfast. Invest. Educ. Enferm. 2016; 34(2):